2013
DOI: 10.1123/ijatt.18.4.34
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Push-Up Exercise Phase and Surface Stability on Activation of the Scapulothoracic Musculature

Abstract: Objective:The purpose of this study was to measure muscle activation during ascending and descending phases of the push-up exercise on both stable and unstable support surfaces.Participants:Fourteen asymptomatic male amateur badminton players. During push-up exercises on stable and unstable bases, muscle activation measurements were collected with phase divisions (ascending and descending phase).Methods:Electromyography (EMG) was utilized to measure activation of the upper trapezius (UT) and lower trapezius (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(31 citation statements)
references
References 13 publications
1
30
0
Order By: Relevance
“…Male participants were predominant (66%). Fourteen studies 15,21,22,[24][25][26][27][28][29][30][31][32][33][34] included only males and one study 14 included only females. Furthermore, 3 studies 32,35,36 specifically included athletes as participants, and one study 21 included participants who were considered as advanced in resistance training.…”
Section: Study Characteristics and Methodological Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Male participants were predominant (66%). Fourteen studies 15,21,22,[24][25][26][27][28][29][30][31][32][33][34] included only males and one study 14 included only females. Furthermore, 3 studies 32,35,36 specifically included athletes as participants, and one study 21 included participants who were considered as advanced in resistance training.…”
Section: Study Characteristics and Methodological Qualitymentioning
confidence: 99%
“…In this review, electrode placement locations varied among studies, and some studies evaluated both upper parts of the SA, whereas some other studies evaluated the lower parts. However, 2 studies 25,32 have evaluated the lower and upper parts of the SA separately, rather than using 1 electrode placement area for the SA. Therefore, we analyzed both parts of the SA and pooled these results together for these 2 studies.…”
Section: Limitationsmentioning
confidence: 99%
“…Only data from healthy participants, who had not undergone therapeutic intervention prior to the evaluation, were included. Regarding EMG variables, 20 studies reported only %MVIC [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41], one study reported only muscle activation ratios [42], and eight studies measured both variables [7,[11][12][13][43][44][45][46]. All the investigations evaluated the UT EMG activity, 13 studies measured MT EMG activity [7,11,13,22,26,30,32,[36][37][38]40,41,46], and 21 measured the LT EMG activity [7,11-13,22,23,25-30, 32,36-41,44,46].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…The exercises analyzed in the articles were the Push Up, Scap Protraction, Pull Up, Press Up, and Plank and Wall Press, with different variations of each one. Fourteen studies evaluated the Push Up exercise and its variations [7,11,12,[24][25][26][28][29][30][31][32]41,42,45], nine studies evaluated the Scap Protraction exercise and its variations [7,13,25,27,33,34,36,43,44], five studies evaluated the Pull Up and its variations [7,37,38,40,46], two studies evaluated the Press Up [13,22], four studies evaluated the Plank and its variations [23,26,35,39], and three studies evaluated the Wall Press and its variations [24,36,43]. Fourteen studies used unstable surfaces as an exercise variation (e.g.…”
Section: Summary Of Activation Ratios and Exercisesmentioning
confidence: 99%
See 1 more Smart Citation